Genetic Dissection of Root Angle of Brassica napus in Response to Low Phosphorus - Duan, Xianjie; Wang, Xiaohua; Jin, Kemo; Wang, Wei; Liu, Haijiang; Liu, Ling; Zhang, Ying; Hammond, John P.; White, Philip J.; Ding, Guangda; Xu, Fangsen; Shi, Lei (Frontiers in Plant Science, 2021)
Plant root angle determines the vertical and horizontal distribution of roots in the soil layer, which further influences the acquisition of phosphorus (P) in topsoil. Large genetic variability for lateral root angle (root angle) was observed in a linkage mapping population (BnaTNDH population) and an association panel of Brassica napus whether at low P (LP) or at optimal P (OP). At LP, the average root angle of both populations became smaller. Nine QTLs at LP and three QTLs at OP for root angle and five QTLs for relative root angle were identified by linkage mapping analysis in BnaTNDH population. Genome-wide association studies (GWAS) revealed 11 single nucleotide polymorphism (SNPs) significantly associated with root angle at LP. The interval of a QTL for root angle at LP on A06 (qLPRA-A06c) overlapped with the confidence region of the leading SNP (Bn-A06-p14439400) significantly associated with the root angle at LP. In addition, a QTL cluster on chromosome C01 associated with root angle, primary root length in ‘pouch and wick’ HTP system, root P concentration in agar system and seed yield in the field was identified in the BnaTNDH population at LP. A total of 87 genes on A06 and 192 genes on C01 were identified within the confidence interval and fourteen genes related to auxin asymmetric redistribution and root developmental process were predicted to be candidate genes. Identification and function analyses of these genes affecting root angle at low P, will be of benefit to the cultivar selection with optimal root system architecture under P deficiency in Brassica napus.